2018
DOI: 10.3390/app8101901
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Forecasting Method for Solar Output Power Based on Variational Mode Decomposition, Deep Belief Networks and Auto-Regressive Moving Average

Abstract: Due to the existing large-scale grid-connected photovoltaic (PV) power generation installations, accurate PV power forecasting is critical to the safe and economical operation of electric power systems. In this study, a hybrid short-term forecasting method based on the Variational Mode Decomposition (VMD) technique, the Deep Belief Network (DBN) and the Auto-Regressive Moving Average Model (ARMA) is proposed to deal with the problem of forecasting accuracy. The DBN model combines a forward unsupervised greedy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Researchers have developed different methods for solar irradiance forecasting, such as statistical approaches using historical data, use of numerical weather prediction (NWP) models, tracking cloud movements from satellite images and tracking cloud movements from direct ground observations using sky cameras [8]. Some reviews on renewable energy forecasting models are given in References [6][7][8][9][10][11] among others. Some notable methods are discussed in the following paragraphs.…”
Section: An Overview Of the Literature On Solar Irradiance Forecastingmentioning
confidence: 99%
“…Researchers have developed different methods for solar irradiance forecasting, such as statistical approaches using historical data, use of numerical weather prediction (NWP) models, tracking cloud movements from satellite images and tracking cloud movements from direct ground observations using sky cameras [8]. Some reviews on renewable energy forecasting models are given in References [6][7][8][9][10][11] among others. Some notable methods are discussed in the following paragraphs.…”
Section: An Overview Of the Literature On Solar Irradiance Forecastingmentioning
confidence: 99%
“…Machine learning methods were successfully applied in PV output prediction models. Xie et al [14] proposed a hybrid short-term forecasting method based on the variational mode decomposition (VMD) technique, the deep belief network (DBN), and the auto-regressive moving average (ARMA) model to improve forecasting accuracy. The results showed that the hybrid forecasting method offers better accuracy and stability than the single prediction methods.…”
Section: Performance Assessmentmentioning
confidence: 99%
“…Step 4: Calculate w according to Equation (17) and update the individual position according to Equations (13) and (16).…”
Section: Dbn Structure Parameters Determined By Mgwo Algorithmmentioning
confidence: 99%
“…It consists of multiple restricted Boltzmann machines (RBMs) and a back propagation (BP) neural network, allowing processing large amounts of data. In recent decades, the DBN has been successfully applied to fault diagnosis, wind speed forecasting, breast cancer classification, and so on [11][12][13][14][15][16]. Due to its advantage in prediction accuracy, in this paper, we introduce the DBN to conduct the PM2.5 concentration prediction.…”
Section: Introductionmentioning
confidence: 99%